Russian “Author’s” Illustration of 1790th Years: a Problem of Reception of the French Analogues: Русская «авторская» иллюстрация 1790-х годов: проблема рецепции французских аналогов - Borshch, Elena (Przegląd Wschodnioeuropejski, 2019)
At the focus of this article is a problem of reception of European visual culture in Russia in XVIII century. The subject of research is the drawings of manuscript “Ovid’s Metamorphoses in faces” of 1790th years from collection of the State Russian museum (St.-Petersburg). Its have been created by I. Tupylev after the order by N. Lvov. There is a search of the European analogues of the Russian drawings in this article. A method of comparative analysis used here. As a result, one of analogues of the Russian illustrations was found. There is comparison the Tupylev’s drawings and engravings of the French edition “Ovid’s Metamorphoses” (1767–1771) in this article. The comparison has proved, that the Russian illustrator repeated compositions of the French illustrations, but did not copy them literally. The result of research is a conclusion about creative character of perception of the traditions of European illustration and professional level of works of Russian artists.